1980
DOI: 10.1063/1.327480
|View full text |Cite
|
Sign up to set email alerts
|

Thermocouple temperature measurements in shock-compressed solids

Abstract: The emf produced by 5-μm-thick foil thermocouples when subjected to shock loading was studied over a stress range from 0.5 to 10 GPa. Thermocouples of either copper and constantan or chromel and alumel were embedded in the host materials, polymethyl methacrylate (PMMA), Epon 828 epoxy, single-crystal Al2O3, or vitreous SiO2. The observed emf history rises to a plateau in a period that varied from less than 100 ns for Al2O3 to about 500 ns for PMMA. Temperatures inferred from the constant-voltage portion of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 17 publications
2
17
0
Order By: Relevance
“…Consequently, it is suggested that other explosives, particularly preased TNT and Tetryl, be instrumented with thermocouples and tested in the same Lrnner as deline.ated in [14] and [15].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Consequently, it is suggested that other explosives, particularly preased TNT and Tetryl, be instrumented with thermocouples and tested in the same Lrnner as deline.ated in [14] and [15].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to PM1A (Plexiglas II, UVA), [15] also contained thermocouple response infor'iqtion for a shocked epoxy, EPON 828. A threshold pressure for enhanced thermocouple output was observed for this material.…”
Section: Recommendationsmentioning
confidence: 99%
See 2 more Smart Citations
“…When the equilibrium condition is satisfied, thermometry measurements are effectively insensitive to properties of the sample (other than temperature). Electrical measurements-such as thermocouples 5 and thermistors 6 -are primary examples of sensorbased thermometry. Each curve indicates the maximum amount of power that can be collected in a particular spectral band, ignoring all losses.…”
Section: Thermometry Backgroundmentioning
confidence: 99%